2010
DOI: 10.1289/ehp.0901229
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Function in Mexican Children Living in a Mining Area and Environmentally Exposed to Manganese

Abstract: BackgroundExcessive exposure to manganese (Mn), an essential trace element, has been shown to be neurotoxic, especially when inhaled. Few studies have examined potential effects of Mn on cognitive functions of environmentally exposed children.ObjectiveThis study was intended to estimate environmental exposure to Mn resulting from mining and processing and to explore its association with intellectual function of school-age children.MethodsChildren between 7 and 11 years of age from the Molango mining district i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
175
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(191 citation statements)
references
References 48 publications
9
175
4
3
Order By: Relevance
“…Similar studies have shown that drinking water containing much lower concentrations of Mn than those found in Bangladesh also caused intellectual impairment in school children 26 . The environmental exposure to Mn from industrial and mining sources, and negative cognitive performance of children were also reported 27,28 . While these studies report deficits in children, the contribution of pre-natal exposure to excess Mn is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have shown that drinking water containing much lower concentrations of Mn than those found in Bangladesh also caused intellectual impairment in school children 26 . The environmental exposure to Mn from industrial and mining sources, and negative cognitive performance of children were also reported 27,28 . While these studies report deficits in children, the contribution of pre-natal exposure to excess Mn is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The waste batteries cause a serious concern due to their toxicity, abundance, and permanence in the environment. Inhabitants living close to mining extraction sites (Riojas-Rodríguez et al 2010) and alloy industries (Menezes-Filho et al 2009) are at threat of extreme Mn exposure. Research investigations on ecological exposure to Mn have effectively applied scalp hair Mn and air Mn as natural and ecological indicator of exposure (Viana et al 2014).…”
Section: Mn Pollution and Health Issuesmentioning
confidence: 99%
“…Las concentraciones más altas de manganeso, se han encontrado en la región minera de Molango en el estado de Hidalgo, con reconocidos efectos sobre la capacidad intelectual en los niños. 43 En otras zonas también se ha encontrado este mineral, incluida la Ciudad de México. 47 La exposición a metales en población infantil es, sin duda, uno de los elementos de la agenda pendiente.…”
Section: 36unclassified